2022
DOI: 10.3390/s22228675
|View full text |Cite
|
Sign up to set email alerts
|

Coal Wall Spalling Mechanism and Grouting Reinforcement Technology of Large Mining Height Working Face

Abstract: To control the problem of coal wall spalling in large mining height working faces subject to mining, considering the Duanwang Mine 150505 fully mechanized working face, the mechanism of coal wall spalling in working faces was investigated by theoretical analysis, numerical simulation and field experiment. Based on analysis of coal wall spalling in the working face, a new grouting material was developed. The stress and plastic zone changes affecting the coal wall, before and after grouting in the working face, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…To this end, scholars have proposed various types of active, passive, and combined supports through a variety of methods [3][4][5]. Overall, the roadway surrounding-rock control can be divided into fve basic support forms, namely, the basic support within the roadway [6,7] (wood bracket, metal bracket, and stone bracket), strengthening support in roadway [8,9] (permanent strengthening support and temporary strengthening support such as single hydraulic prop), roadway side support [10,11] (wood crib, dense pillar, gangue wall, concrete wall, and flling wall), grouting modifcation [12][13][14] (ordinary portland cement, Marysan, and new polymer organic and inorganic modifed materials), nonsingle support form [15][16][17] (above two and multiple combined support technologies). Te surroundingrock supporting theory of coal mine roadway mainly includes suspension theory, composite beam theory, composite arch theory, maximum horizontal stress theory, and surrounding rock strength strengthening theory [18].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, scholars have proposed various types of active, passive, and combined supports through a variety of methods [3][4][5]. Overall, the roadway surrounding-rock control can be divided into fve basic support forms, namely, the basic support within the roadway [6,7] (wood bracket, metal bracket, and stone bracket), strengthening support in roadway [8,9] (permanent strengthening support and temporary strengthening support such as single hydraulic prop), roadway side support [10,11] (wood crib, dense pillar, gangue wall, concrete wall, and flling wall), grouting modifcation [12][13][14] (ordinary portland cement, Marysan, and new polymer organic and inorganic modifed materials), nonsingle support form [15][16][17] (above two and multiple combined support technologies). Te surroundingrock supporting theory of coal mine roadway mainly includes suspension theory, composite beam theory, composite arch theory, maximum horizontal stress theory, and surrounding rock strength strengthening theory [18].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that under the disturbance of repeated mining the roof dynamic load is high, and the subsidence of the end face roof is large. In addition, Song et al [14] used the finite element method, Jiao et al [15] and Kong et al [16] used the discrete element method, and Wang et al [17] and Liu and Chen [18] used the finite difference method to numerically calculate the plastic zone or failure range of the coal rock mass in front of the coal wall of the working face. They summarized that the main controllable factors to roof fall and rib scattering follow the order of coal > support strength > mining height > distance to face > local force.…”
Section: Introductionmentioning
confidence: 99%